2006
DOI: 10.1590/s1413-70542006000400014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidade de natuneem sobre Tetranychus urticae Koch (Acari: Tetranychidae) e ácaros predadores da família Phytoseiidae

Abstract: RESUMOA toxicidade de diferentes concentrações de Natuneem a Tetranychus urticae Koch e a dois ácaros predadores, Euseius alatus De Leon e Phytoseiulus macropilis (Banks), foi estudada. Foi avaliada a toxicidade sobre ovos, e o efeito residual e repelente, sobre adultos. O tratamento dos ovos consistiu na imersão em diluições de Natuneem por cinco segundos, e o efeito residual e repelente sobre adultos consistiu na imersão de discos de folhas de Canavalia ensiformes (L.) DC. também em diluições por cinco segun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…For neem based products, it has been demonstrated that selectivity towards natural enemies is related to formulation and concentration (Silva & Martinez 2004, Mourão et al 2004, Brito et al 2006b. For lime sulphur, recent studies showed the same tendency (Tuelher 2006, Soto 2009).…”
Section: Discussionmentioning
confidence: 93%
“…For neem based products, it has been demonstrated that selectivity towards natural enemies is related to formulation and concentration (Silva & Martinez 2004, Mourão et al 2004, Brito et al 2006b. For lime sulphur, recent studies showed the same tendency (Tuelher 2006, Soto 2009).…”
Section: Discussionmentioning
confidence: 93%
“…De acordo com Duso et al (2008), os produtos naturais azadiractina e rotenona proporcionaram 99,3 e 62,9% de inviabilidade de ovos de T. urticae, respectivamente, em feijão, nas concentrações comerciais de 4,5 g de i.a e 18 ml de i.a/ha, recomendadas. Natuneem a 1% reduziu em 97,5% a viabilidade de ovos de T. urticae em C. ensiformes (BRITO et al, 2006). Segundo Attia et al (2012), o extrato de A. sativum nas concentrações 0,36 e 0,74 mg/L, também foi efetivo na redução da fecundidade de T. urticae.…”
Section: Toxicidade De Acaricidas Para Ovos Deunclassified
“…Reduction of TSSM population after neem derivates usage as reported here was attributed mostly for mortality, repellency, reduction of the oviposition and decrease in egg eclosion (DIMETRY et al, 1993;BRITO et al, 2006;CASTIGLIONI et al, 2002). Although a greater concentration of the neem oil (2%) was used in our study than the majority of previous ones, an apparent reduction of the neem effi ciency was observed after second and third spraying (Figure 1).…”
Section: Fertilizationmentioning
confidence: 55%
“…The results were conducted during a more extensive period (three sprayings) and directly in the plants. In general, the majority of the studies were conducted just after one spraying in leaf discs (DIMETRY et al, 1993;BRITO et al, 2006, CASTIGLIONI et al, 2002. In the same way when neem was applied directly on plants (carrots, Daucus carota L.) TSSM mortality was in shorter levels (DUCHOVSKIENE et al, 2008).…”
Section: Fertilizationmentioning
confidence: 99%